English Department Students' Attitudes towards Teaching Profession (Journal of the College of Basic Education, 2019)
Attitudes refer to the inside tendency and thoughts that reflect when a person is displayed to some phenomenon. The main objectives of the present research are to: discover EFL students' attitudes towards teaching profession, and find out if there is a statistical significant difference in attitudes between students at the college of Education "Ibn Rushd" and students at the college of Education for women in Baghdad University? and to discover, if there is a statistical significant difference in attitudes between males and females? The sample is 90 students are selected from in-service training teachers \ fourth stage at college of education Ibn_Rushd and college of education for women. The researcher uses an attitude scale as a tool which consists of a 20 item "likert scale" consists of six subscales. Each one has a statement that pertains to a particular aspect of possibility and assessing teacher’s vocational attitudes. The results show that EFL female students' as well as males do have real tendency toward teaching profession, the Mean values shows that no significant difference between the two colleges (college of education for women & college of Ibn Rushd) about their attitude which means both of them show favourable attitude toward teaching profession.